1999
DOI: 10.1103/physrevd.59.114022
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive rare decays of heavy baryons to light baryons:ΛbΛγandΛb

Abstract: The rare decays ⌳ b →⌳␥ and ⌳ b →⌳l ϩ l Ϫ (lϭe,) are examined. We use QCD sum rules to calculate the hadronic matrix elements governing the decays. The ⌳ polarization in the decays is analyzed and it is shown that the polarization parameter in ⌳ b →⌳␥ does not depend on the values of hadronic form factors. The energy spectrum of ⌳ in ⌳ b →⌳l ϩ l Ϫ is given. ͓S0556-2821͑99͒02511-4͔

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The decay rate and lepton side angular distribution has also been studied in the SM and in several extensions of the SM (NP models) in Refs. [3][4][5][6][7][8][9][10][11][12]. If the Λ b is produced polarised, a much larger number of observables are measurable.…”
Section: Introductionmentioning
confidence: 99%
“…The decay rate and lepton side angular distribution has also been studied in the SM and in several extensions of the SM (NP models) in Refs. [3][4][5][6][7][8][9][10][11][12]. If the Λ b is produced polarised, a much larger number of observables are measurable.…”
Section: Introductionmentioning
confidence: 99%
“…The glueball spectrum has attracted much attention more than three decades [1], and it has been widely investigated by using various non-perturbative methods. For example, from first principles calculation by using lattice QCD [2][3][4][5][6], by using flux tube model [7] as well as by using QCD sum rules [8][9][10]. For more information, please refer to review papers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in the SM and in the context of NP have been reported in Refs. [26][27][28][29][30][31][32][33]. The b → μ + μ − angular distributions for polarized b were recently worked out in [34].…”
Section: Introductionmentioning
confidence: 99%